Factors Influencing Sertu Cleansing Integrity in Halal Logistics (Journal of Business Management and Accounting, 2016)
Nowadays, the integrity of halal product status is important for Muslim consumers. Sertu cleansing operations is to ensure that transportation and logistics carrying halal products are assured with no occurrence of contamination from non-halal sources in halal logistics. However, the study on sertu cleansing in Malaysia is still low. Therefore, this concept paper attempts to discuss factors in sertu cleansing integrity as stated in Malaysian Standards MS1500: 2009 for halal food production, preparing, handling, and storage, and MS2400: 2010 for halalan-toiyibban assurance pipeline or known as halal supply chain management. The factors in halal cleansing that influence the halal product integrity such as: sertu procedure; process or method of sertu cleansing; people engaged  in  these  activities;  and  the  sertu  cleansing  products.  This  paper  generates awareness and provides better understanding on the factors influencing sertu cleansing in assuring halal integrity of halal food products and other related products.